1=(x+1)ln(x+1)+xln(x)

Simple and best practice solution for 1=(x+1)ln(x+1)+xln(x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1=(x+1)ln(x+1)+xln(x) equation:


Simplifying
1 = (x + 1) * ln(x + 1) + xln(x)

Reorder the terms:
1 = (1 + x) * ln(x + 1) + xln(x)

Reorder the terms:
1 = (1 + x) * ln(1 + x) + xln(x)

Reorder the terms for easier multiplication:
1 = ln(1 + x)(1 + x) + xln(x)

Multiply (1 + x) * (1 + x)
1 = ln(1(1 + x) + x(1 + x)) + xln(x)
1 = ln((1 * 1 + x * 1) + x(1 + x)) + xln(x)
1 = ln((1 + 1x) + x(1 + x)) + xln(x)
1 = ln(1 + 1x + (1 * x + x * x)) + xln(x)
1 = ln(1 + 1x + (1x + x2)) + xln(x)

Combine like terms: 1x + 1x = 2x
1 = ln(1 + 2x + x2) + xln(x)
1 = (1 * ln + 2x * ln + x2 * ln) + xln(x)
1 = (1ln + 2lnx + lnx2) + xln(x)

Multiply lnx * x
1 = 1ln + 2lnx + lnx2 + lnx2

Combine like terms: lnx2 + lnx2 = 2lnx2
1 = 1ln + 2lnx + 2lnx2

Solving
1 = 1ln + 2lnx + 2lnx2

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '-1ln' to each side of the equation.
1 + -1ln = 1ln + 2lnx + -1ln + 2lnx2

Reorder the terms:
1 + -1ln = 1ln + -1ln + 2lnx + 2lnx2

Combine like terms: 1ln + -1ln = 0
1 + -1ln = 0 + 2lnx + 2lnx2
1 + -1ln = 2lnx + 2lnx2

Add '-2lnx' to each side of the equation.
1 + -1ln + -2lnx = 2lnx + -2lnx + 2lnx2

Combine like terms: 2lnx + -2lnx = 0
1 + -1ln + -2lnx = 0 + 2lnx2
1 + -1ln + -2lnx = 2lnx2

Add '-2lnx2' to each side of the equation.
1 + -1ln + -2lnx + -2lnx2 = 2lnx2 + -2lnx2

Combine like terms: 2lnx2 + -2lnx2 = 0
1 + -1ln + -2lnx + -2lnx2 = 0

Add '-1' to each side of the equation.
1 + -1ln + -2lnx + -1 + -2lnx2 = 0 + -1

Reorder the terms:
1 + -1 + -1ln + -2lnx + -2lnx2 = 0 + -1

Combine like terms: 1 + -1 = 0
0 + -1ln + -2lnx + -2lnx2 = 0 + -1
-1ln + -2lnx + -2lnx2 = 0 + -1

Combine like terms: 0 + -1 = -1
-1ln + -2lnx + -2lnx2 = -1

Reorder the terms:
1 + -1ln + -2lnx + -2lnx2 = -1 + 1

Combine like terms: -1 + 1 = 0
1 + -1ln + -2lnx + -2lnx2 = 0

The solution to this equation could not be determined.

See similar equations:

| 2x-3=10x+19 | | 3D+2W=18 | | y+1(9+24)-21=21 | | 3xy-2x+4= | | 12a/8/5 | | 6x+2=2x+18 | | 5g+7g=10g | | 2a+b=210 | | (10)(9.8)sin(30)= | | (5x-3y)(x^6-4xy+2y^2)= | | 6x^2-25=x^2 | | 4(2c-1)-4=4c+4 | | 37+3y-13=11y-11-3y | | 16=2(L+2)+2W | | 4x+4=6(0.7x+1.8) | | 17x+-32=-11x | | 3x-17=90 | | 0.04(n-1.5)=0.04n-0.06 | | 12x-10=9x-14 | | (-3.25)(-1.56)= | | 14y^15/7y^2 | | 3*cos(x)-2-4*sin(x)=0 | | 2(9s+5)-3s=3(5s+2)-8 | | 3cos(x)-2-4Sin(x)=0 | | (x+6)(y+8)= | | 5(2p+10)=10(p+2)-40 | | 9(x+6y)+9(4x+5y)= | | (-6xy)(8xy)= | | ln(y)=0.63 | | 5z^5q^2+2z^5q= | | 2.1(3+4x)-8.1=1.5(2+4x) | | 16.4+0.5x=9.4-1.1x+12 |

Equations solver categories